Phylogeography, population structure and evolution of coral-eating butterflyfishes (Family Chaetodontidae, genus Chaetodon, subgenus Corallochaetodon) - Waldrop, E.; Hobbs, J.; Randall, J.; Di Battista, Joseph; Rocha, L.; Kosaki, R.; Berumen, M.; Bowen, B. (2016)
Aim: This study compares the phylogeography, population structure and evolution of four butterflyfish species in the Chaetodon subgenus Corallochaetodon, with two widespread species (Indian Ocean – C. trifasciatus and Pacific Ocean – C. lunulatus), and two species that are largely restricted to the Red Sea (C. austriacus) and north-western (NW) Indian Ocean (C. melapterus). Through extensive geographical coverage of these taxa, we seek to resolve patterns of genetic diversity within and between closely related butterflyfish species in order to illuminate biogeographical and evolutionary processes. Location: Red Sea, Indian Ocean and Pacific Ocean. Methods: A total of 632 individuals from 24 locations throughout the geographical ranges of all four members of the subgenus Corallochaetodon were sequenced using a 605 bp fragment (cytochrome b) of mtDNA. In addition, 10 microsatellite loci were used to assess population structure in the two widespread species. Results: Phylogenetic reconstruction indicates that the Pacific Ocean C. lunulatus diverged from the Indian Ocean C. trifasciatus approximately 3 Ma, while C. melapterus and C. austriacus comprise a cluster of shared haplotypes derived from C. trifasciatus within the last 0.75 Myr. The Pacific C. lunulatus had significant population structure at peripheral locations on the eastern edge of its range (French Polynesia, Johnston Atoll, Hawai'i), and a strong break between two ecoregions of the Hawaiian Archipelago. The Indian Ocean C. trifasciatus showed significant structure only at the Chagos Archipelago in the central Indian Ocean, and the two range-restricted species showed no population structure but evidence of recent population expansion. Main conclusions: Patterns of endemism and genetic diversity in Corallochaetodon butterflyfishes have been shaped by (1) Plio-Pleistocene sea level changes that facilitated evolutionary divergences at biogeographical barriers between Indian and Pacific Oceans, and the Indian Ocean and Red Sea, and (2) semi-permeable oceanographic and ecological barriers working on a shorter time-scale. The evolution of range-restricted species (Red Sea and NW Indian Ocean) and isolated populations (Hawai'i) at peripheral biogeographical provinces indicates that these areas are evolutionary incubators for reef fishes.